Automated Resource Management System based on Kubernetes Technology - Jirayus Sithiyopasakul; Tuanjai Archevapanich; Boonchana Purahong; Paisan Sithiyopasakul; C. Benjangkaprasert (My University, 2021)
The purpose of this research is intended to study and analyze the Kubernetes technology using the processes of performance evaluation by inspecting how many requests and responses could the server handle. According to the ability of Kubernetes technology, there is no systematic measure of performance despite the Kubernetes is currently in use broadly. Therefore, this paper proposed to test out the system by measuring the effectiveness according to a structured process by studying such measurement variables including the number of requests per second, number of responses to requests, and resource extension period with Kubernetes technology. Which from the testing and analysis of all three variables as mentioned, it is possible to know the efficiency of the Kubernetes technology in such a similar environment. Moreover, the testing experiment could display a piece of information on the dashboard for visualization and analytic purposes.
Keywords: Cloud Computing and Resource Management; Technology and Data Analysis; Innovation in Digital Healthcare Systems